STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN DALAM MENANAMKAN NILAI IMAN DAN KARAKTER KRISTIANI PADA PESERTA DIDIK - Egal Ningrat; Grasela Elisabet Meilani Sumbaoni; Putri Allo; Yulianti Paranduk; Tasik Pasau (CV. ADIBA AISHA AMIRA, 2026)
Christian Religious Education plays a crucial role in shaping students' faith and character. The learning process focuses not only on imparting knowledge about the teachings of faith but also on instilling moral and spiritual values ​​that can be applied in everyday life. This study aims to examine Christian Religious Education's learning strategies for instilling Christian faith and character in students. The research method used is a qualitative approach with a descriptive approach through literature review. Data were obtained from various literature sources such as books, scientific journals, and documents relevant to the research topic. The results indicate that effective learning strategies in Christian Religious Education include student-centered learning, Bible discussion and reflection, experiential learning, and the instilling of Christian values ​​in school life. Implementing these strategies can help students understand, internalize, and practice the values ​​of faith in everyday life, thus forming a strong Christian character.